Novel swine biliary dilatation model with temperature-controlled endobiliary radiofrequency ablation: An effective tool for training in EUS-guided biliary drainage - Oh, Dongwook (Endosc Ultrasound, 2020)
BACKGROUND AND OBJECTIVES: EUS-guided biliary drainage (EUS-BD) is used as a rescue method after failed endoscopic retrograde cholangiography. However, it is considered a technically challenging procedure. Phantoms and ex vivo biliary dilatation models have been used to enhance the learning of EUS-BD, but they provide a limited level of realism. The aim of this study was to develop a swine biliary dilatation model that uses temperature-controlled endobiliary radiofrequency ablation (EB-RFA) for training in EUS-BD. MATERIALS AND METHODS: Target temperature-controlled (80°C at 7 or 10 W for 60–120 s) EB-RFA was performed on seven pigs. Two weeks after the EB-RFA, EUS examination was performed to confirm biliary dilatation, and EUS-BD was then attempted by performing a hepaticogastrostomy (HGS) or cholecystogastrostomy (CGS). RESULTS: Twelve sessions of EB-RFA (11 at the distal common bile duct [CBD] and one at the proximal CBD) were successfully performed on the seven pigs. There were no immediate postprocedural adverse events. Two weeks after the procedures, clinical signs of jaundice were observed in all the pigs. EUS examination revealed massive intrahepatic and extrahepatic biliary dilatations in all the pigs, and EUS-BD was attempted in the same session. HGS was performed on six pigs. Technical success was achieved in five of the six pigs (83.3%). Technical failure in HGS occurred during the stent deployment, and CGS was successfully performed on one pig. CONCLUSIONS: Our study shows that EB-RFA is an effective minimally invasive method for creating biliary dilatation models. It may be considered suitable for training in EUS-BD.